Geoquímica dos solos e sedimentos da bacia do rio Pelotas - Silva, Plínio Emanoel Rodrigues (2021)
Population growth and human activities have affected the environment, causing an imbalance in the concentration of trace elements in the ecosystem. Due to the biogeochemical characteristics of sediments, part of these elements is adsorbed and deposited at the bottom of water courses. Thus, obtaining geochemical reference values for trace elements and analyzing watershed sediments consist in an important method to investigate the contamination of the environment by trace elements. This study aims to analyze the concentration of trace elements in the sediments and soil of the Pelotas River basin, define the geochemical reference values for the watershed and carry out an environmental analysis, based on quality indexes. For this purpose, soil samples were collected from eight points in an area with little human interference, at depths of 0 – 20 and 20 – 40 cm, and it was calculated the geochemical reference value for each trace element, by various methods, in order to define the best value. The sediments were collected quarterly, from May 2013 to February 2014, from six points of the Pelotas river and two points of its tributaries. It was determined the total concentration of the elements Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Na, Ni, P, Pb and Zn, as well as the contents of total organic carbon and pH. The bioavailable concentration of the elements Cr, Cu, Mn, Ni, P, Pb and Zn was also determined. From the results, the contamination factor of the elements Co, Cr, Cu, Mn, Ni, Pb and Zn, the degree of contamination and the potential ecological risk index of the basin were calculated. Both the soil and the sediments of the basin displayed higher concentrations of the elements Fe, Ca, K, Mg, Mn and Na, which are elements that present little environmental risk and are more associated with the geogenic origin. The elements Cd, Cr, Ni and Pb were the ones with the lowest concentrations, which is a good indication, since such elements are associated with anthropogenic pollution. The basin presented a high geochemical reference value for the elements Cd and Co, when compared to the geochemical reference value defined in other studies, being an indication for studies related to the source material of the basin's soils. The importance of determining the reference values on regional scales was verified.